Catalyst slurry for electrochemical synthesis of hydrogen peroxide, gas diffusion electrode and preparation method thereof

The gas diffusion electrode prepared by the two-component slurry preparation method and the slit extrusion method solves the problems of catalyst slurry stability and uniformity, and achieves efficient yield and electrode preparation quality of electrochemical synthesis of hydrogen peroxide.

CN119615229APending Publication Date: 2025-03-14ZHEJIANG YIPAI TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411792409.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-07
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing catalyst slurry has poor stability and is uneven, making it difficult to effectively apply to gas diffusion electrodes for electrochemical synthesis of hydrogen peroxide.

Method used

Using a two-component slurry preparation method, a uniform and stable catalyst slurry is formed by mixing surfactant and hydrophobic agent, combining the dispersion of carbon powder and thickener, and is loaded to the surface of hydrophobic carbon paper by slit extrusion method, and sintering is carried out to prepare a gas diffusion electrode.

Benefits of technology

The uniform stability and uniform load of the catalyst slurry are achieved, the preparation quality of the gas diffusion electrode and the yield of hydrogen peroxide are improved, and the pore structure is more uniform, which is suitable for the mass transfer process of electrosynthesis of hydrogen peroxide.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615229A_ABST
    Figure CN119615229A_ABST
Patent Text Reader

Abstract

The invention provides catalyst slurry for electrochemical synthesis of hydrogen peroxide, a gas diffusion electrode and a preparation method of the gas diffusion electrode, and belongs to the technical field of hydrogen peroxide electrosynthesis. The preparation method of the catalyst slurry comprises the following steps: (1) dissolving a surfactant 1 in water, adding a water repellent agent, and mixing to obtain a slurry component 1; (2) dispersing carbon powder in a mixed solvent, then sequentially adding a surfactant 2 and a thickening agent, and mixing and dispersing to obtain a slurry component 2; and (3) adding the slurry component 1 into the slurry component 2, and mixing to obtain the catalyst slurry. The gas diffusion electrode prepared by adopting the bi-component slurry and a slit extrusion coating process is more uniform in pore structure, and is beneficial to a mass transfer process in electrosynthesis of hydrogen peroxide, that is, the prepared gas diffusion electrode has more advantages compared with a traditional electrode form.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of hydrogen peroxide electrosynthesis, and in particular to a catalyst slurry, a gas diffusion electrode and a preparation method thereof for electrochemically synthesizing hydrogen peroxide. Background Art

[0002] The huge global demand for wastewater treatment, papermaking and green chemical synthesis has made hydrogen peroxide (H2O2) one of the most important chemicals in many industries. This chemical is usually produced on a large scale by the anthraquinone oxidation process (AOP), which requires the direct use of hydrogen and oxygen and the use of expensive palladium catalysts, followed by cumbersome separation steps to remove large amounts of organic waste. Therefore, the AOP method is not only costly and cumbersome, but also has safety issues in storage and transportation. Due to the urgent need for greener processes, recent research has turned to exploring electrochemical routes to produce H2O2 at a lower cost.

[0003] Electrosynthesis of H2O2 can decompose the H2O / O2 redox reaction into two half-cell reactions (cathode: 2e - +2H2O+O2→HO2 - +OH - and anode: H2O→1 / 2O2+2H + +2e - ), followed by an ion recombination process (HO2 - +H + →H2O2 and OH - +H + →H2O). In order to achieve efficient conversion, it is necessary to select electrocatalysts with high activity and selectivity. Anodic hydrogen oxidation reaction (HOR) usually adopts iridium catalysts, which provide efficient H2O to H2O conversion at a small overpotential. + The conversion rate of the two-electron oxygen reduction reaction at the cathode (2e - ORR) often uses carbon materials such as graphene, carbon nanotubes, porous carbon or XC72 as electrocatalysts, which have a great influence on 2e - The pathway is highly selective.

[0004] In order to make the cathode 2e - In order for the carbon material catalyst of the ORR reaction to play a better role, it is particularly important to prepare a uniform and stable catalyst slurry and evenly load it on the substrate surface to form an electrode. However, the slurry obtained by the traditional catalyst slurry preparation process (such as stirring and ultrasound) usually has problems such as wall hanging, quicksand, and easy stratification when placed. Therefore, how to obtain a uniform and stable catalyst slurry and apply it to the gas diffusion electrode for electrochemical synthesis of hydrogen peroxide is a technical problem that needs to be solved at present. Summary of the invention

[0005] The object of the present invention is to provide a catalyst slurry, a gas diffusion electrode and a preparation method thereof for electrochemical synthesis of hydrogen peroxide, so as to solve the technical problems of poor stability and non-uniformity of the existing catalyst slurry.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide, comprising the following steps:

[0008] (1) dissolving surfactant 1 in water, and then adding a hydrophobic agent to mix to obtain slurry component 1;

[0009] (2) dispersing carbon powder in a mixed solvent, and then sequentially adding surfactant 2 and thickener to mix and disperse to obtain slurry component 2;

[0010] (3) Slurry component 1 is added to slurry component 2 and mixed to obtain catalyst slurry.

[0011] Furthermore, the surfactant 1 and the surfactant 2 independently contain one or more of cetyltrimethylammonium bromide, sodium dodecyl sulfate, polyethylene glycol cetyl ether, polyethylene glycol dialkyl ether and polyoxyethylene alkylamide; the mass ratio of the surfactant 1 to the hydrophobic agent is 1-10:1-10, and the mass ratio of the surfactant 2 to the carbon powder is 1-2:1-10.

[0012] Further, the carbon powder comprises one or more of XC72, acetylene black, pearl black, Ketjen black, carbon nanotubes and graphitized carbon, and the hydrophobic agent comprises one or more of polytetrafluoroethylene, polyvinylidene fluoride, perfluorooctane sulfonyl compound and polydimethyl diamine;

[0013] The mass ratio of the hydrophobic agent to the carbon powder is 1-2:1-10.

[0014] Furthermore, the thickener comprises one or more of polyethylene glycol, polyvinyl alcohol, sodium alginate, polyvinyl pyrrolidone and carboxymethyl cellulose, and the average molecular weight of the thickener is between 1000 and 1000000; the mass ratio of the thickener to the carbon powder is 1:1-100.

[0015] Furthermore, the mixed solvent is a mixed solvent of water and alcohol, the alcohol includes one or more of ethanol, n-propanol and isopropanol, and the mass ratio of water to alcohol is 1-5:1-5.

[0016] Furthermore, in step (1), the mixing time is 2 to 4 hours;

[0017] In the step (2), the dispersion time of adding surfactant 2 is 1 to 2 hours, and the dispersion time of adding thickener is 1 to 2 hours; the mixing and dispersion is carried out in a sand mill, the dispersion speed is 1000 to 2000 rpm, and the dispersion time is 2 to 4 hours;

[0018] In the step (3), the adding method is dropwise addition, and the mixing time is 1 to 4 hours;

[0019] The solid content of the catalyst slurry is 5-25%.

[0020] The invention also provides a catalyst slurry for electrochemical synthesis of hydrogen peroxide.

[0021] The present invention also provides a method for preparing a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide, comprising the following steps:

[0022] The catalyst slurry for electrochemical synthesis of hydrogen peroxide is loaded onto the surface of hydrophobic carbon paper by a slit extrusion method, and then sintered in an inert atmosphere to obtain a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide;

[0023] The slot extrusion method includes: the distance between the coating die and the substrate is 500-1000 μm, the coating speed is 10-50 cm / s, the wet film thickness after coating is 10-100 μm, the slurry drying time after coating is 30-60 minutes, and the drying temperature is 60-100°C.

[0024] Furthermore, the sintering temperature is 350-450° C., the sintering time is 1-4 hours, and the contact angle of the gas diffusion electrode after the sintering is 120°-160°.

[0025] The invention also provides a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide.

[0026] Beneficial effects of the present invention:

[0027] The dispersion process of the two-component slurry in the present invention is simple and can be mass-produced, which improves production efficiency, and the dispersed slurry has a small particle size and the catalyst is evenly dispersed. At the same time, the slurry is adapted to the slit extrusion coating process, has stable fluidity and suitable viscosity, ensures the uniformity and thickness consistency of the coating, and improves the preparation quality of the gas diffusion electrode. Finally, compared with traditional electrodes, the gas diffusion electrode prepared by the two-component slurry and slit extrusion coating process of the present invention has a more uniform pore structure, which is conducive to the mass transfer process in the electrosynthesis of hydrogen peroxide, that is, the prepared gas diffusion electrode is more advantageous than the traditional electrode form. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1Schematic diagram of the electrolytic cell structure and reaction principle used for the electrode prepared by the catalyst slurry of the present invention; wherein the catalyst slurry is loaded on the hydrophobic carbon paper and sintered to prepare the cathode gas diffusion electrode, and a two-electron oxygen reduction reaction occurs to generate HO2 - +OH - , passes through the anion membrane to the solid electrolyte, and reacts with the H produced by the hydrogen oxidation reaction at the anode gas diffusion electrode. + Combined at the solid electrolyte to form neutral H2O2;

[0029] Figure 2 The present invention is a flow chart for preparing the catalyst slurry;

[0030] Figure 3 The particle size distribution diagram of the catalyst slurry of Example 1, Example 2 and Comparative Example 1 of the present invention;

[0031] Figure 4 The viscosity curves of the catalyst slurries of Example 1, Example 2 and Comparative Example 2 of the present invention are shown;

[0032] Figure 5 The data graphs are of the concentration of hydrogen peroxide generated at different times by the electrodes corresponding to the catalyst slurries of Example 1, Example 2 and Comparative Example 1 of the present invention;

[0033] Figure 6 It is a data graph showing the concentration of hydrogen peroxide generated at different times by the electrodes corresponding to the catalyst slurries of Example 1, Example 2, Example 3, Example 4, Example 5 and Comparative Example 3 of the present invention;

[0034] Figure 7 The contact angle data diagram of the electrodes corresponding to the slurries of Examples 1-5 and Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide, comprising the following steps:

[0036] (1) dissolving surfactant 1 in water, and then adding a hydrophobic agent to mix to obtain slurry component 1;

[0037] (2) dispersing carbon powder in a mixed solvent, and then sequentially adding surfactant 2 and thickener to mix and disperse to obtain slurry component 2;

[0038] (3) Slurry component 1 is added to slurry component 2 and mixed to obtain catalyst slurry.

[0039] In the present invention, the surfactant 1 and the surfactant 2 independently contain one or more of cetyltrimethylammonium bromide, sodium dodecyl sulfate, polyethylene glycol cetyl ether, polyethylene glycol dialkyl ether and polyoxyethylene alkyl amide, preferably cetyltrimethylammonium bromide and / or sodium dodecyl sulfate; the mass ratio of the surfactant 1 to the hydrophobic agent is 1-10:1-10, preferably 2-8:2-8, and further preferably 3-7:3-7; the mass ratio of the surfactant 2 to the carbon powder is 1-2:1-10, preferably 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 2:1.

[0040] In the present invention, the carbon powder comprises one or more of XC72, acetylene black, pearl black, Ketjen black, carbon nanotubes and graphitized carbon, preferably one or more of acetylene black, pearl black and Ketjen black; the hydrophobic agent comprises one or more of polytetrafluoroethylene, polyvinylidene fluoride, perfluorooctane sulfonyl compound and polydimethyl diamine, preferably polytetrafluoroethylene and / or polyvinylidene fluoride;

[0041] The mass ratio of the hydrophobic agent to the carbon powder is 1-2:1-10, preferably 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 2:1.

[0042] In the present invention, the thickener comprises one or more of polyethylene glycol, polyvinyl alcohol, sodium alginate, polyvinyl pyrrolidone and carboxymethyl cellulose, preferably one or more of polyethylene glycol, polyvinyl alcohol and sodium alginate; the average molecular weight of the thickener is between 1000 and 1000000, preferably between 2000 and 100000; the mass ratio of the thickener to the carbon powder is 1:1 to 100, preferably 1:10 to 90, and more preferably 1:20 to 80.

[0043] In the present invention, the mixed solvent is a mixed solvent of water and alcohol, the alcohol comprises one or more of ethanol, n-propanol and isopropanol, preferably ethanol and / or n-propanol; the mass ratio of water to alcohol is 1-5:1-5, preferably 2-4:2-4, and more preferably 1:1.

[0044] In the present invention, in step (1), the mixing time is 2 to 4 hours, preferably 2 hours.

[0045] In the present invention, in the step (2), the time for adding the surfactant 2 and dispersing is 1 to 2 hours, preferably 1 hour; the time for adding the thickener and dispersing is 1 to 2 hours, preferably 1 hour; the mixing and dispersing is carried out in a sand mill, and the dispersing speed is 1000 to 2000 rpm, preferably 1500 rpm; the dispersing time is 2 to 4 hours, preferably 2 hours.

[0046] In the present invention, in the step (3), the adding method is preferably dropwise addition, and the mixing time is 1 to 4 hours, preferably 1 to 3 hours.

[0047] In the present invention, the solid content of the catalyst slurry is 5 to 25%, preferably 10 to 20%, and more preferably 15%.

[0048] The invention also provides a catalyst slurry for electrochemical synthesis of hydrogen peroxide.

[0049] The present invention also provides a method for preparing a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide, comprising the following steps:

[0050] The catalyst slurry for electrochemical synthesis of hydrogen peroxide is loaded onto the surface of hydrophobic carbon paper by a slit extrusion method, and then sintered in an inert atmosphere to obtain a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide;

[0051] The slot extrusion method includes: the distance between the coating die and the substrate is 500-1000 μm, the coating speed is 10-50 cm / s, the wet film thickness after coating is 10-100 μm, the slurry drying time after coating is 30-60 minutes, and the drying temperature is 60-100°C.

[0052] In the present invention, the slot extrusion method is preferably: the distance between the coating die and the substrate is 600-800 μm, the coating speed is 20-40 cm / s, the wet film thickness after coating is 20-80 μm, the slurry drying time after coating is 40-50 min, and the drying temperature is 70-80°C.

[0053] In the present invention, the sintering temperature is 350-450°C, preferably 360-380°C, and more preferably 370°C; the sintering time is 1-4h, preferably 2-3h; the contact angle of the gas diffusion electrode after sintering is 120°-160°, preferably 140°-160°.

[0054] The invention also provides a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide.

[0055] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0056] Example 1

[0057] A method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide comprises the following steps:

[0058] Step (1) Preparation of slurry component 1: Disperse 4.28 g of polyoxyethylene alkylamide into 34.28 g of ultrapure water, heat at 80°C for 30 min to dissolve it, then add 4.28 g of polytetrafluoroethylene powder, stir and disperse for 2 h to obtain slurry component 1; (2) Preparation of slurry component 2: Disperse 10 g of polyoxyethylene alkylamide into 34.28 g of ultrapure water, heat at 80°C for 30 min to dissolve it, then add 4.28 g of polytetrafluoroethylene powder, stir and disperse for 2 h to obtain slurry component 1; XC72 carbon powder was dissolved in a mixed solvent of 119.22 g ethanol and 236.49 g ultrapure water, 8 g polyethylene glycol hexadecyl ether was added, and the mixture was stirred for 1 h to mix the slurry, 1 g polyvinyl pyrrolidone with a molecular weight of 300,000 was added, and the mixture was stirred for 1 h to mix the slurry, and the slurry was further dispersed in a sand mill at a speed of 1500 rpm for 2 h, and a slurry component 2 with a suitable particle size was obtained by dispersion; (3) Two-component slurry mixing: slurry component 1 was slowly added dropwise to slurry component 2, and a magnetic stirrer was used to stir the materials to make them evenly mixed, at a speed of 500 rpm. After the addition was completed, stirring was continued for 1 h to obtain the final catalyst slurry;

[0059] Preparation of gas diffusion electrode:

[0060] (4) Catalyst loading: The catalyst slurry is loaded onto the surface of the hydrophobic carbon paper by slit extrusion. The slit extrusion process includes: a distance between the coating die and the substrate of 600 μm, a coating speed of 25 cm / s, a wet film thickness of 20 μm after coating, a slurry drying time of 30 min after coating, and a drying temperature of 60°C; (5) High-temperature sintering treatment: The catalyst-loaded carbon paper is sintered in a protective atmosphere at a sintering temperature of 400°C and a sintering time of 2 h. After sintering, a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide can be obtained.

[0061] Example 2

[0062] A method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide comprises the following steps:

[0063] Step (1) Preparation of slurry component 1: Disperse 4.28 g of polyoxyethylene alkylamide into 34.28 g of ultrapure water, heat at 80°C for 30 min to dissolve it, then add 4.28 g of polytetrafluoroethylene powder, stir and disperse for 2 h to obtain slurry component 1; (2) Preparation of slurry component 2: Disperse 10 g of polyoxyethylene alkylamide into 34.28 g of ultrapure water, heat at 80°C for 30 min to dissolve it, then add 4.28 g of polytetrafluoroethylene powder, stir and disperse for 2 h to obtain slurry component 1; XC72 carbon powder was dissolved in a mixed solvent of 119.22 g ethanol and 236.49 g ultrapure water, 8 g polyethylene glycol hexadecyl ether was added, and the mixture was stirred for 1 h to mix the slurry, 1 g polyethylene glycol with a molecular weight of 80,000 was added, and the mixture was stirred for 1 h to mix the slurry, and the slurry was further dispersed in a sand mill at a speed of 1500 rpm for 2 h, and a slurry component 2 with a suitable particle size was obtained by dispersion; (3) Two-component slurry mixing: slurry component 1 was slowly added dropwise to slurry component 2, and a magnetic stirrer was used to stir the materials to make them evenly mixed, at a speed of 500 rpm. After the addition was completed, stirring was continued for 1 h to obtain the final catalyst slurry;

[0064] Preparation of gas diffusion electrode:

[0065] (4) Catalyst loading: The catalyst slurry is loaded onto the surface of the hydrophobic carbon paper by slit extrusion. The slit extrusion process includes: a distance between the coating die and the substrate of 600 μm, a coating speed of 25 cm / s, a wet film thickness of 20 μm after coating, a slurry drying time of 30 min after coating, and a drying temperature of 60°C; (5) High-temperature sintering treatment: The catalyst-loaded carbon paper is sintered in a protective atmosphere at a sintering temperature of 400°C and a sintering time of 2 h. After sintering, a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide can be obtained.

[0066] Example 3

[0067] A method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide. The preparation method is the same as that of Example 1, except that surfactant 1 is hexadecyltrimethylammonium bromide and surfactant 2 is sodium dodecyl sulfate.

[0068] The preparation of the gas diffusion electrode is the same as that of Example 1, except that the sintering temperature is 350°C.

[0069] Example 4

[0070] A method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide, the preparation method is the same as that in Example 1.

[0071] Preparation of gas diffusion electrode:

[0072] (4) Catalyst loading: The catalyst slurry is loaded onto the surface of the hydrophobic carbon paper by slit extrusion. The slit extrusion process includes: a distance between the coating die and the substrate of 1000 μm, a coating speed of 50 cm / s, a wet film thickness of 50 μm after coating, a slurry drying time of 40 min after coating, and a drying temperature of 80°C; (5) High-temperature sintering treatment: The catalyst-loaded carbon paper is sintered in a protective atmosphere at a sintering temperature of 380°C and a sintering time of 2 h. After sintering, a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide can be obtained.

[0073] Example 5

[0074] A method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide. The preparation method is the same as that of Example 1, except that a thickener is polyvinyl alcohol with a molecular weight of 40,000.

[0075] The preparation of the gas diffusion electrode is the same as in Example 1.

[0076] Comparative Example 1

[0077] The difference between Comparative Example 1 and Example 1 is that polyethylene glycol hexadecyl ether is not added in step (2), and other proportions and conditions are the same as those in Example 1, which is used to compare the effects of the addition of surfactant on the catalyst slurry state and the performance of the rear electrode.

[0078] Comparative Example 2

[0079] The difference between Comparative Example 2 and Example 1 is that polyvinyl pyrrolidone is not added in step (2), and other proportions and conditions are the same as those in Example 1, which is used to compare the effects of the thickener addition on the catalyst slurry state and the rear electrode performance.

[0080] Comparative Example 3

[0081] Comparative Example 3 is a conventional catalyst slurry preparation method, 10g XC72 carbon powder is dissolved in a mixed solvent of 119.22g ethanol and 270.77g ultrapure water, 8g polyethylene glycol hexadecyl ether is added, 1g of a thickener polyvinyl pyrrolidone with a molecular weight of 300000 is added, stirred for 1h to mix the slurry, 4.28g polytetrafluoroethylene powder is added, stirred for 1h to mix the slurry, and then ultrasonicated for 2h to obtain a catalyst slurry. The preparation process of the gas diffusion electrode is the same as that of Example 1.

[0082] The catalyst slurries prepared in Examples 1-5 and Comparative Examples 1-3 were evaluated, including the testing and evaluation of the appearance, particle size, and viscosity of the slurries. In addition, the gas diffusion electrodes prepared in Examples 1-5 and Comparative Examples 1-3 were cut into appropriate sizes (25 cm 2 ), assembled into a battery for hydrogen peroxide yield test.

[0083] The gas diffusion electrodes prepared by the slurries of Examples 1-5 and Comparative Examples 1 and 3 were assembled into Figure 1 The hydrogen peroxide yield test was conducted in the electrolytic cell shown. Pure water was circulated at a rate of 10 mL / min through the anode; pure water was circulated at a rate of 10 mL / min through the solid electrolyte; and humidified oxygen was circulated at a rate of 250 mL / min through the cathode. 2 Hydrogen peroxide was prepared by constant current. 1 mL of the reaction solution was taken out every 15 min using a pipette (from the 750 mL beaker at the outlet of the solid electrolyte). The hydrogen peroxide yield was measured by UV-visible spectrophotometry at 400 nm. The results are shown in Figure 5 and Figure 6 .

[0084] Figure 3 The particle size distribution diagrams of Example 1, Example 2 and Comparative Example 1 of the present invention are shown in FIG. Figure 3The particle size distribution of the slurry is as follows: the particle size of the slurry in Example 1 is D10=0.149μm, D50=0.386μm, and D90=1.44μm; the particle size of the slurry in Example 2 is D10=3.68μm, D50=6.69μm, and D90=11.6μm; the particle size of the slurry in Comparative Example 1 is D10=13.4μm, D50=32.6μm, and D90=88.4μm. It can be seen from Example 1 and Comparative Example 1 that after the surfactant polyethylene glycol hexadecyl ether is added to the slurry, the particle size is significantly reduced, and the slurry has good fluidity, without quicksand and wall hanging. It can be seen from Example 1 and Example 2 that the surfactant polyethylene glycol hexadecyl ether is added to the slurry, but different thickeners are used. Example 1 uses polyvinyl pyrrolidone, and Example 2 uses polyethylene glycol. The slurry particle size using polyvinyl pyrrolidone is smaller and the slurry dispersion is more uniform.

[0085] Figure 4 The viscosity curves of Example 1, Example 2 and Comparative Example 2 of the present invention are shown in FIG. Figure 4 The viscosity curve of the slurry is: -1 Under the conditions, the slurry viscosity of Example 1 is 14.7mPa·s; the slurry viscosity of Example 2 is 44.4mPa·s; and the slurry viscosity of Comparative Example 2 is 5.83mPa·s. It can be seen from Example 1 and Comparative Example 2 that after the thickener polyvinyl pyrrolidone is added to the slurry, the viscosity increases, which is more conducive to coating by the slit extrusion equipment. It can be seen from Example 1 and Example 2 that the slurry uses different thickeners, Example 1 uses polyvinyl pyrrolidone, and Example 2 uses polyethylene glycol. The corresponding viscosity of the slurry using polyethylene glycol is higher, indicating that polyethylene glycol has a more obvious thickening effect on the slurry, but the resulting slurry particle size is larger, which may affect the subsequent electrode performance.

[0086] Figure 5 The data graphs are for the hydrogen peroxide concentrations generated by the electrodes corresponding to the slurries of Example 1, Example 2, and Comparative Example 1 at different times. The slurry of Comparative Example 2 cannot be coated onto the surface of hydrophobic carbon paper by slit extrusion due to its low viscosity. The slurries of Example 1, Example 2, and Comparative Example 1 can be coated onto the surface of hydrophobic carbon paper by slit extrusion to prepare gas diffusion electrodes for hydrogen peroxide yield testing. Figure 5 It can be seen from the hydrogen peroxide production rate in Example 1 that the hydrogen peroxide production rate is the highest. A larger slurry particle size may have a negative impact on the final gas diffusion electrode performance, while a smaller slurry particle size has a more uniform catalyst dispersion and the prepared gas diffusion electrode has better performance.

[0087] Figure 6 The data graph of the concentration of hydrogen peroxide generated by the electrodes corresponding to the slurries of Examples 1-5 and Comparative Example 3 at different times. Figure 6The hydrogen peroxide production rate of all examples is higher than that of comparative example 3, indicating that the catalyst utilization rate in the two-component slurry is higher, which is better than the traditional catalyst slurry preparation process. At the same time, the two-component slurry has no wall hanging and quicksand phenomenon, and no stratification phenomenon occurs after long-term storage, and the slurry is stable.

[0088] Figure 7 The contact angle data of the electrodes corresponding to the slurries of Examples 1-5 and Comparative Example 3 are shown in FIG. According to the contact angle data, the contact angle of the gas diffusion electrode made from the slurries of Examples 1-5 is greater than that of the gas diffusion electrode made from the slurry of Comparative Example 3, and the electrodes corresponding to the slurries of the Examples are more hydrophobic, which is conducive to the production of hydrogen peroxide.

[0089] It can be seen from the above embodiments that the present invention provides a catalyst slurry, a gas diffusion electrode and a preparation method thereof for the electrochemical synthesis of hydrogen peroxide. The dispersion process of the two-component slurry of the present invention is simple, and can be mass-produced, which improves production efficiency, and the dispersed slurry has a small particle size and the catalyst is evenly dispersed. At the same time, the slurry is adapted to the slit extrusion coating process, has stable fluidity and suitable viscosity, ensures the uniformity and thickness consistency of the coating, and improves the preparation quality of the gas diffusion electrode. Finally, compared with traditional electrodes, the gas diffusion electrode prepared by the two-component slurry and slit extrusion coating process of the present invention has a more uniform pore structure, which is conducive to the mass transfer process in the electrosynthesis of hydrogen peroxide, that is, the prepared gas diffusion electrode is more advantageous than the traditional electrode form.

[0090] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide, characterized in that: The following steps are involved: (1) dissolving surfactant 1 in water, and then adding a hydrophobic agent to mix to obtain slurry component 1; (2) dispersing carbon powder in a mixed solvent, and then sequentially adding surfactant 2 and thickener to mix and disperse to obtain slurry component 2; (3) Slurry component 1 is added to slurry component 2 and mixed to obtain catalyst slurry.

2. The method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide according to claim 1, characterized in that: The surfactant 1 and the surfactant 2 independently contain one or more of cetyltrimethylammonium bromide, sodium dodecyl sulfate, polyethylene glycol cetyl ether, polyethylene glycol dialkyl ether and polyoxyethylene alkylamide; the mass ratio of the surfactant 1 to the hydrophobic agent is 1-10:1-10, and the mass ratio of the surfactant 2 to the carbon powder is 1-2:1-10.

3. The method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide according to claim 1 or 2, characterized in that: The carbon powder comprises one or more of XC72, acetylene black, pearl black, Ketjen black, carbon nanotubes and graphitized carbon, and the hydrophobic agent comprises one or more of polytetrafluoroethylene, polyvinylidene fluoride, perfluorooctane sulfonyl compound and polydimethyl diamine; The mass ratio of the hydrophobic agent to the carbon powder is 1-2:1-10.

4. The method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide according to claim 3, characterized in that: The thickener comprises one or more of polyethylene glycol, polyvinyl alcohol, sodium alginate, polyvinyl pyrrolidone and carboxymethyl cellulose, and the average molecular weight of the thickener is between 1000 and 1000000; the mass ratio of the thickener to the carbon powder is 1:1-100.

5. The method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide according to claim 1, 2 or 4, characterized in that: The mixed solvent is a mixed solvent of water and alcohol, the alcohol includes one or more of ethanol, n-propanol and isopropanol, and the mass ratio of water to alcohol is 1-5:1-5.

6. The method for preparing a catalyst slurry for electrochemical synthesis of hydrogen peroxide according to claim 5, characterized in that: In the step (1), the mixing time is 2 to 4 hours; In the step (2), the dispersion time of adding surfactant 2 is 1 to 2 hours, and the dispersion time of adding thickener is 1 to 2 hours; the mixing and dispersion is carried out in a sand mill, the dispersion speed is 1000 to 2000 rpm, and the dispersion time is 2 to 4 hours; In the step (3), the adding method is dropwise addition, and the mixing time is 1 to 4 hours; The solid content of the catalyst slurry is 5-25%.

7. Catalyst slurry for electrochemical synthesis of hydrogen peroxide prepared by the preparation method according to any one of claims 1 to 6.

8. A method for preparing a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide, characterized in that: The following steps are involved: The catalyst slurry for electrochemical synthesis of hydrogen peroxide according to claim 7 is loaded onto the surface of hydrophobic carbon paper by a slit extrusion method, and then sintered under an inert atmosphere to obtain a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide; The slot extrusion method includes: the distance between the coating die and the substrate is 500-1000 μm, the coating speed is 10-50 cm / s, the wet film thickness after coating is 10-100 μm, the slurry drying time after coating is 30-60 minutes, and the drying temperature is 60-100°C.

9. The method for preparing a gas diffusion electrode for electrochemical synthesis of hydrogen peroxide according to claim 8, characterized in that: The sintering temperature is 350-450° C., the sintering time is 1-4 hours, and the contact angle of the gas diffusion electrode after the sintering is 120°-160°.

10. A gas diffusion electrode for electrochemical synthesis of hydrogen peroxide prepared by the preparation method according to claim 8 or 9.